2012
DOI: 10.1093/annonc/mdr042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a novel nurse-led prechemotherapy education intervention (ChemoEd) on patient distress, symptom burden, and treatment-related information and support needs: results from a randomised, controlled trial

Abstract: ChemoEd holds promise to improve patient treatment-related concerns and some physical/psychological outcomes; however, further research is required on more diverse patient populations to ensure generalisability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
106
0
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(126 citation statements)
references
References 38 publications
5
106
0
15
Order By: Relevance
“…Provision of sufficient pre-chemotherapy information including side effects and self-care strategies was proven to reduce certain treatment-related concerns and physical and psychosocial outcomes (Aranda et al, 2012). A study of Chinese breast cancer patients showed that side effects of chemotherapy and their management were given a higher priority among the information needed (Lee et al, 2004).…”
Section: Hk Chan and S Ismailmentioning
confidence: 99%
“…Provision of sufficient pre-chemotherapy information including side effects and self-care strategies was proven to reduce certain treatment-related concerns and physical and psychosocial outcomes (Aranda et al, 2012). A study of Chinese breast cancer patients showed that side effects of chemotherapy and their management were given a higher priority among the information needed (Lee et al, 2004).…”
Section: Hk Chan and S Ismailmentioning
confidence: 99%
“…These findings are similar to findings of current study except mouth or throat problem and infection. 15 In this study, the five most troublesome non physical side effects were: affects work, home duties, feel anxious, affects family, affects partner and affects social activities. A study done in Australia supports the findings of current study as the study revealed anxiety, effect on family, effect on social lives as most bothering non physical side effects of chemotherapy.…”
mentioning
confidence: 71%
“…Kada su u pitanju psihološki simptomi, žene sa ginekološkim karcinomom pate od depresije, anksioznosti ili čak suicidalnih ideja [5,6]. Psihološki problemi mogu prouzrokovati negativna osećanja kao što su frustracija, bes, tuga i sramota, dodatno pogoršavajući generalno loše psihološko stanje [7]. Pojedini autori navode da psihološke promene mogu zavisiti i od lokalizacije malignog tumora.…”
unclassified
“…Pojedini autori navode da psihološke promene mogu zavisiti i od lokalizacije malignog tumora. Žene lečene zbog karcinoma grlića materice više pate zbog izmenjene slike tela, imaju manje izraženu anksioznost od pacijentkinja lečenih zbog karcinoma jajnika, dok one lečene zbog karcinoma tela materice imaju najmanje izražene psihološke poremećaje [7]. Pregled literature ukazuje na deficit znanja o prevalenciji, težini i ozbiljnosti simptoma koji prate ove pacijentkinje [3].…”
unclassified